Public policy sport in Chile: traffic to the democratization - Franklin Castillo Retamal; Felipe Canan; Fernando Starepravo (Universidade Estadual do Oeste do Paraná, 2017)
The text presents a documentary review in relation to the development of the public politics in sport and recreation that the Chilean State has come developing from starts of the 19th century. The documentary analysis allows to explain the content of one or several texts and the document is foundation to elaborate a general comment relate to the central subject of agreement to the situation or historical moment in which it contextualized the information. The data expose the evolution that the approaches related with public politics in sport in Chile have had until the current deployment of initiatives that try to establish a democratic and participatory process of the community in the lifting of proposals of agreement to the interests, needs and possibilities that the It detects like viable to improve. The review allows concluding that it does necessary establish a structural frame that was integrator and directed to the attainment of the understanding of the importance of the public politics in this field as like this also to strengthen the dialogue between the organisms that interact in virtue of the social welfare.